Review of the collection «100 years of the Kabardino-Balkarian Republic. Archival chronicle. – Nalchik: Publishing house M. and V. Kotlyarovs, 2022. 384 pp. + 80 pp. on» - Alexey Kh, Abazov (Kavkazologiya, 2023)
The overview of the collection “100 years of the Kabardino-Balkarian Republic. Archival Chroni-cle“, published by the KBR Archival Service in 2022 as part of the Documents Testify project and dedicated to the 100th anniversary of the statehood of Kabardino-Balkarian Republic. The paper includes 329 archival documents and 169 photographs on the history of the republic from 1922 to 2022. A description of the documents placed in the collection is given: regulatory legal acts and records of state authorities of the KBR (KBAO, KBASSR) in the field of national-state construc-tion, the creation and activities of educational and scientific institutions, the organization of health care and the cultural and leisure sphere, the main trends in the development of enterprises of the agricultural and industrial complex, documents with elements of statistical generalization, correspondence about the most significant events in the region’s history, etc. The documents of the appendix of the collection are described, which contains photographic illustrative material, information about the heroes of the Soviet Union, the heroes of Socialist Labor, full holders of the Order of Glory, and holders of the Order of Labor Glory. Attention is drawn to the fact that the publication is addressed to a wide range of researchers: historians, local historians, journalists, writers, students and schoolchildren, as well as everyone who is interested in the history of the peoples of Kabardino-Balkaria.